Factors Associated With Health-Related Quality of Life of Parents Who Lost Their Only Child: A Cross-Sectional Study in Central China - Rong, Chao; Zheng, Li-Jie; Zhang, Qian; Cao, Yi-Dan; Shen, Shu-Hua; Gao, Zheng-Qing; Wan, Duo; Shen, Wei-Wei; Xu, Cai-Ming; Wang, Xiao-Lan (Frontiers in Public Health, 2020)
Purpose: The number of families who lost their only child was over one million in 2012 in China, and it is growing rapidly every year. Without their only child, they will inevitably worry about their health and life for their later years. It is important to explore the quality of life and influencing factors of the parents. Methods: The cluster sampling method was adopted to select the participants in Wuhu city, Anhui province, central China. The generalized linear regression models were performed to analyze factors influencing EQ-VAS scores. Results: The parents with different monthly income (P = 0.001) and self-rated health status (P < 0.001) had different EQ-VAS scores. Educational level, self-rated health status, number of chronic diseases, depression and having grandchildren were significantly associated with their EQ-VAS score. Conclusion: The government should encourage public medical institutions to provide convenient health management and medical services to this vulnerable group. Priority treatment should be given to the parents who already have multiple diseases. The parents who were depressed should be given timely intervention. The government should give more financial subsidies to the parents who need to raise their grandchildren.